RUNX1 gene expression changes in the placentas of women smokers (2021)
The placenta can be affected by environmental factors, such as exposure to cigarette smoke. This exposure in the fetal context is considered a risk factor for the development of short‑term postnatal diseases, such as asthma. Asthma is an inflammatory disease characterized by predominant acquisition of CD4 T lymphocytes (TLs) of the Th2 type. Transcription factors such as GATA binding protein 3 (GATA3) and STAT6 actively participate in the differentiation of virgin TLs towards the Th2 profile, while transcription factors such as STAT1, T‑Box transcription factor 21 (T‑BET), RUNX1 and RUNX3 participate in their differentiation towards the Th1 profile. The objective of the current study was to evaluate the impact of exposure to cigarette smoke on the gene expression of STAT1, T‑BET, GATA3, IL‑4, RUNX1 and RUNX3 during the gestation period, and to determine whether the expression levels of these genes are associated with changes in global methylation. STAT1, GATA3, RUNX1 and RUNX3 protein and mRNA expression levels in the placental tissue of women smokers and non‑smoking women were determined via immunohistochemistry and quantitative PCR (qPCR) respectively. Additionally, T‑BET and IL‑4 mRNA expression levels were determined by qPCR. On the other hand, global methylation was determined via ELISA. In the present study, significant increases were observed in RUNX1 transcription factor expression in placentas from women smokers when compared with placentas of non‑smoking women. Similarly, significant increases in the expression of GATA3, IL‑4 and RUNX3 mRNA were observed. The changes in gene expression were not associated with changes in the global methylation levels. Finally, a higher frequency of low‑birth‑weight infants were identified in cases of exposure to cigarette smoke during pregnancy when compared with infants not exposed to cigarette smoke during pregnancy. Thus, the data of the present study contributed to the understanding of the genetic and clinical impacts of exposure to cigarette smoke during pregnancy and its importance in maternal and fetal health.